If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(a + 3) = a + -2(a + -1x) Reorder the terms: x + -1(3 + a) = a + -2(a + -1x) x + (3 * -1 + a * -1) = a + -2(a + -1x) x + (-3 + -1a) = a + -2(a + -1x) Reorder the terms: -3 + -1a + x = a + -2(a + -1x) -3 + -1a + x = a + (a * -2 + -1x * -2) -3 + -1a + x = a + (-2a + 2x) Combine like terms: a + -2a = -1a -3 + -1a + x = -1a + 2x Add 'a' to each side of the equation. -3 + -1a + a + x = -1a + a + 2x Combine like terms: -1a + a = 0 -3 + 0 + x = -1a + a + 2x -3 + x = -1a + a + 2x Combine like terms: -1a + a = 0 -3 + x = 0 + 2x -3 + x = 2x Solving -3 + x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + x + -2x = 2x + -2x Combine like terms: x + -2x = -1x -3 + -1x = 2x + -2x Combine like terms: 2x + -2x = 0 -3 + -1x = 0 Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| 192-7x=29x+16 | | x^8-6x^6=0 | | 11-9x=128-30x | | 223+175= | | 123+175= | | x^4+2x^3+x^2=0 | | -15-6x=5-10x | | 5x-7=2x+3x-7 | | 4x^2=36x | | 490-x=23 | | 2h+3h^2-2h^3=2 | | 2h+3h^2-2h^3=3 | | -5x=8 | | 8g=5g-21 | | 17a=4a-9 | | 3g+17.2=11.6g | | 49-3x=6x+19 | | 5n=53-2.6n | | 6p=60-4p | | 4a+13=69-4a | | 4y=56.7-2.3y | | 3d=42-4d | | 3d=42-4dt | | 3t=27-2.4t | | 3cd-c-3ed^2+ed=0 | | 6b=38.5+0.5b | | 3x^3-22x^2+48x-32=0 | | 4.1x-2(1.3x-4)=0.5 | | x^2+24x+28=0 | | 0.54+54x=234 | | 0.54+54x=234+6x^2 | | 2y+3=7 |